2013
DOI: 10.1007/s10995-013-1308-8
|View full text |Cite
|
Sign up to set email alerts
|

What New Mothers Need to Know: Perspectives from Women and Providers in Georgia

Abstract: Identifying the educational and resource needs of new mothers is of paramount importance in developing programs to improve maternal and child health outcomes. The primary purpose of this study was to explore the educational needs of new mothers and identify opportunities to enhance healthcare providers' current educational efforts. A two-part methodology was utilized to qualitatively explore the topic of parenting information needs for new mothers in Georgia. Data collection included information from 11 focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 45 publications
0
46
0
3
Order By: Relevance
“…A very recent focus group study among new mothers by Gazmararian et al (2014) explicitly indicated that new mothers encounter a significant informational deficiency, especially on very basic, daily infant care information.…”
Section: Health Information Needs Among Mothersmentioning
confidence: 99%
“…A very recent focus group study among new mothers by Gazmararian et al (2014) explicitly indicated that new mothers encounter a significant informational deficiency, especially on very basic, daily infant care information.…”
Section: Health Information Needs Among Mothersmentioning
confidence: 99%
“…A recent US study reported that mothers had difficulty accessing and understanding maternal and infant health information although educational materials already exist [14]. The internet may be and will be, more critically, an important resource to provide parents and health professionals with essential information including breastfeeding techniques, benefits of breastfeeding and self or peer-care tools such as selfmonitoring modules and peer supporting network programs [15].…”
Section: Introductionmentioning
confidence: 99%
“…Present educational parenting materials may be at levels inappropriate to meet the needs of families. 67 As researchers and practitioners, we must also think critically about providing information that perpetuates misinformation. Underlying extinction interventions is the premise that bedtime noncompliance has been trained by the behaviors of the parents.…”
Section: Misinformationmentioning
confidence: 99%
“…32 Little evidence exists relating to sleep intervention uptake and culture; however, there are examples of how other parenting practices are influenced by culture. For example, breastfeeding, co-sleeping and transitioning to solid foods are deeply embedded within cultural practices 67 and may oppose the general narrative in the wider community. In some cultures, leaving a child to sleep alone is considered "bad parenting," 78 which has significant implications for treatment, especially in relation to extinction interventions.…”
Section: Different Cultural Practicesmentioning
confidence: 99%
See 1 more Smart Citation